Learning actions, objects and types of interaction: A methodological analysis of expansive learning among pre-service teachers - Rantavuori, Juhana; Engeström, Yrjö; Lipponen, Lasse (Frontline Learning Research, 2016)
The paper analyzes a collaborative learning process among Finnish pre-service teachers planning their own learning in a self-regulated way. The study builds on cultural-historical activity theory and the theory of expansive learning, integrating for the first time an analysis of learning actions and an analysis of types of interaction. We examine the theory of expansive learning as a possible conceptual and methodological framework for understanding this type of collaborative learning. The task of the paper is primarily methodological. We believe that cultural-historical activity theory needs to be turned into methods and procedures of systematic empirical analysis, and this article examines one such methodological solution. At the same time, we aim to uncover some substantive dynamics of expansive learning in collaborative teacher education oriented at open-ended problems and tasks. An almost complete expansive mini-cycle of learning actions appeared in the pre-service teachers’ meeting. However, an analysis of the steps of formation of the shared object revealed a more complex iterative process. As the expansive learning process moved epistemically from questioning to analysis, modeling and implementation, it also moved interactionally from coordination to cooperation and communication. Yet there was no mechanical correspondence between specific learning actions and specific types of interaction. Transitions and disturbances were crucial for the dynamics of expansive learning. A full assessment of a potentially expansive mini-cycle of learning calls for extending the time scale of the analysis.